2014
DOI: 10.1161/circgenetics.114.000682
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variations Associated With Recurrent Venous Thrombosis

Abstract: Background— The prediction of recurrent venous thrombosis using individual genetic risk predictors has proven to be challenging. The aim of this study was to assess whether multiple genetic single nucleotide polymorphism (SNP) analysis would predict recurrent venous thrombosis. Methods and Results— Patients with a first venous thrombosis were followed for a recurrent venous thrombosis up to 2009 (MEGA follow-up study), which occurred in 608 out of 4100 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 23 publications
4
23
2
Order By: Relevance
“…Our results, at least partially, explain that FVL alone may not be a strong contributing factor for VTE recurrence; however, in combination with other risk factors it can better predict the risk of VTE recurrence. These results are in agreement with previous findings showing that FVL is not a strong risk factor for VTE recurrence [38,39].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our results, at least partially, explain that FVL alone may not be a strong contributing factor for VTE recurrence; however, in combination with other risk factors it can better predict the risk of VTE recurrence. These results are in agreement with previous findings showing that FVL is not a strong risk factor for VTE recurrence [38,39].…”
Section: Discussionsupporting
confidence: 94%
“…Suggesting that combined analysis of these polymorphisms and FVL may better predict VTE recurrence. Recurrent VTE is a multifactorial disease and combination of multiple genetic risk factors has been shown to better predict recurrence compared to presence of individual genetic risk factors [38]. Our results, at least partially, explain that FVL alone may not be a strong contributing factor for VTE recurrence; however, in combination with other risk factors it can better predict the risk of VTE recurrence.…”
Section: Discussionmentioning
confidence: 58%
“…Previously, there was a single study in which this polymorphism has been studied for its role in primary deep vein thrombosis (DVT) and no association was found between TLR9 rs5743836 polymorphism and risk of DVT among a European population [27]. Recent studies have suggested that the risk factors for primary and recurrent VTE may differ [37, 38]. Furthermore, the above-mentioned study [27] included only male patients, while our results suggest that TLR 9 rs5743836 polymorphism is only associated with risk of VTE recurrence in female patients but not in male patients.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there are confirmed genetic determinants of deep venous throbosis. Inherited protein C, S, von Willebrand factor, and antithrombin deficiencies include specific single nucleotide polymorphisms and haplotypes [73][74][75][76][77][78][79]. The role of inherited thrombophilic disorders in the risk of severe COVID-19 has not as yet been emphasized or investigated to date.…”
Section: Coagulation and Thrombosis In Covid-19mentioning
confidence: 99%